2) We need to transform it into linear ODEObserve the exponent of y, it's n=2. So we'll use substitution "v=y^{1-n}=y^{1-2}=y^{-1}" 3) So we have"v= \\dfrac{1}{y}""v'= (\\dfrac{1}{y})\t'""v'=-( \\dfrac{1}{y^2}\t)y'=-v^2y'" In (*) substitute "y'=-( \\dfrac{1}{v^2}\t)v'" and "y= \\dfrac{1}{v}""\\dfrac{-v}{v^2}\t+ \\dfrac{1}{xv}+ \\dfrac{1}{x^2v^2}=0" .... (**) this is a first-order linear ODE.4) New substitutionv = x uwhere u=u(x) and that's all we need to know about "u" for nowv' = xu' + uback to (**)"- \\dfrac{(xu'+u)}{x^2u^2}\t+ \\dfrac{1}{x^2u}\t+ \\dfrac{1}{(x^4u^2)}\t=0" or expanded"- \\dfrac{u'}{xu^2}\t- \\dfrac{1}{x^2u}\t+\\dfrac{1}{(x^2u)}+ \\dfrac{1}{(x^4u^2)}\t=0" 5) Solve for u' two middle terms are canceled:"-\\dfrac{u'}{(xu^2)}+\\dfrac{1}{(x^4u^2)}=0" multiply by xu²"-u'+ \\dfrac{1}{x^3}\t=0""u'= \\dfrac{1}{x^3}" 6) Integrate with respect to x"u=\\int( \\dfrac{1}{x^3}\t)dx""u=- \\dfrac{1}{2x^2}+C"
7) Substitute back "u= \\dfrac{v}{x}""\\dfrac{v}{x}\t=- \\dfrac{1}{2x^2}+C" 8) Multiply by x"v=- \\dfrac{1}{2x}+Cx" 9) Substitute back "v= \\dfrac{1}{y}""\\dfrac{1}{y}\t=- \\dfrac{1}{(2x)}+Cx""\\dfrac{1}{y}\t=- \\dfrac{1}{(2x)}+ \\dfrac{2Cx^2}{2x}= \\dfrac{(2Cx^2-1)}{2x}"
"y= \\dfrac{2x}{2Cx^2-1}"
Since C is constant, for simplicity of solution we can introduce a new constantC₁ = 2C so finally"y= \\dfrac{2x}{(C_1x^2-1)}"
Comments
Leave a comment